Glacial geomorphology and paleoglaciation patterns in Shaluli Shan, the southeastern Tibetan Plateau - Evidence for polythermal ice cap glaciation - Fu, Ping; Harbor, Jonathan M.; Stroeven, Arjen P.; Hattestrand, Clas; Heyman, Jakob; Zhou, Liping (Geomorphology, 2013)
Glacial geomorphological mapping from satellite imagery and field investigations provide the basis for a reconstruction of the extent and style of glaciation of the Shaluli Shan, a mountainous area on the southeastern Tibetan Plateau. Our studies provide evidence for multiple glaciations, including the formation of regional ice caps and valley glaciers. The low-relief topography within the Shaluli Shan, the Haizishan Plateau, and Xinlong Plateau display zonal distributions of glacial landforms that is similar to those imprinted by Northern Hemisphere ice sheets during the last glacial cycle, indicating the presence of regional, polythermal ice caps. Abundant alpine glacial landforms occur on high mountain ranges. The pattern of glaciated valleys centered on high mountain ranges and ice-scoured low relief granite plateaus with distinctive patterns of glacial lineations indicate a strong topographic control on erosional and depositional patterns by glaciers and ice caps. In contrast to the Shaluli Shan, areas farther north and west on the Tibetan Plateau have not yielded similar landform evidence for regional ice caps with complex thermal basal conditions. Such spatial differences across the Tibetan Plateau are the result of variations in climate and topography that control the extent and style of glaciations and that reinforce the importance of detailed geomorphological mapping for understanding paleoclimate variations and characteristics of former glaciations. (C) 2012 Elsevier B.V. All rights reserved. Geography, Physical Geosciences, Multidisciplinary SCI(E) 5 ARTICLE 66-78 182